A Needs Analysis for the Development of a Canva-Based E-Module to Foster Critical Thinking Skills Among Elementary School Students - Handayani, Rani; Yusuf Muslihin, Heri; Hidayat, Syarif (Papanda Publisher, 2025)
The involvement of technology in the learning process can present its attraction for students in improving skills, one of which is critical thinking skills. This study aims to analyze the need to develop e-modules based on the Canva application to foster the critical thinking skills of elementary school students. The background of this research is based on the importance of critical thinking skills in the digital era, the potential of e-modules as an innovative learning resource, and the ease of use of Canva in creating visual materials. The research method used was a comprehensive literature study of scientific journal articles, books, conference proceedings, and other relevant sources. The results of the study identified the characteristics of effective e-modules to foster critical thinking skills, the potential of Canva application in fulfilling these characteristics (especially in visual aspects and ease of use), as well as challenges in its development and implementation in elementary schools (including the limitations of Canva's interactive features, the need for a mature instructional design, teacher availability and skills, technology access gaps, and effectiveness evaluation). This study concludes that the development of Canva-based e-modules has significant potential as an engaging learning resource. Still, their effectiveness in fostering critical thinking skills depends on proper instructional design and efforts to overcome various implementation challenges. Further empirical research is needed to validate the effectiveness of this approach in educational practice.